Handbook of aging and the social sciences - Ferraro, Kenneth F.; Carr, Deborah (Deborah S.); Freedman, Vicki A.; Idler, Ellen L.; Wilmoth, Janet M. (Janet May) (Handbooks of aging., 2021)
Handbook of Aging and the Social Sciences, Ninth Edition, provides a comprehensive synthesis of the latest research findings in the science of aging. The complexities of population dynamics, cohort succession and policy changes modify the world and its inhabitants in ways that must be vigilantly monitored. Completely revised, this edition not only includes the foundational, classic themes of aging research, but also a rich array of emerging topics and perspectives that advance the field in exciting ways. New topics include families, immigration, social factors and cognition, caregiving, neighborhoods and built environments, natural disasters, religion and health, and sexual behavior, among others. This book will serve as a useful resource and an inspiration to those searching for ways to contribute to the aging enterprise.